2022
DOI: 10.1097/scs.0000000000008724
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Syndrome of the Trephined and Reconstructive Implications

Abstract: Syndrome of the trephined (SoT) is a severe complication following decompressive craniectomy resulting in neurological decline which can progress to aphasia, catatonia, and even death. While cranioplasty can reverse neurological symptoms of SoT, awareness of SoT is poor outside of the neurosurgery community. The authors performed a systematic review of the literature on SoT with a focus on reconstructive implications. Search terms “syndrome of the trephined” and “sunken flap syndrome” were applied to PubMed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Its diagnosis supposes the precedent of craniectomy accompanied by neurological symptoms such as motor weakness, cognitive deficit, language deficit, altered level of consciousness, headache, seizures, cranial nerve alterations, psycho-emotional symptoms, in a patient who has not undergone cranioplasty. The exacerbation of these symptoms seems to be related to postural changes, especially those that involve standing vertically, as well as the progressive sinking of the skin flap [15][16][17][18].…”
Section: Postcranectomy Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Its diagnosis supposes the precedent of craniectomy accompanied by neurological symptoms such as motor weakness, cognitive deficit, language deficit, altered level of consciousness, headache, seizures, cranial nerve alterations, psycho-emotional symptoms, in a patient who has not undergone cranioplasty. The exacerbation of these symptoms seems to be related to postural changes, especially those that involve standing vertically, as well as the progressive sinking of the skin flap [15][16][17][18].…”
Section: Postcranectomy Syndromementioning
confidence: 99%
“…On the other hand, considering the established relationship between the pressure and volume of cerebrospinal fluid and its pathophysiology, there could be a greater risk of developing alterations in patients with pressure changes in the third ventricle [14]. Its treatment is cranioplasty, before which the symptoms improve, as well as elements such as cerebrospinal fluid pressure at the lumbar level and cerebral perfusion pressure return to normal levels, suggesting a causal relationship to the defect and its change [15][16][17][18][19]. In the presence of hydrocephalus after craniectomy, the shunt does not seem to represent an improvement in patients, instead leading to greater neurological deterioration that is based on the understanding of the patho-physiology of the syndrome that we have so far [16].…”
Section: Postcranectomy Syndromementioning
confidence: 99%
“…Cranioplasty is a common procedure to repair a skull defect resulting from a previous operation or injury [ 1 , 2 ]. While the procedure is primarily performed to protect the brain from outside forces, cranioplasty can improve neurological function, enhance glymphatic fluid circulation, and restore intracranial pressure adaptations and cerebrospinal fluid circulation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also highlighted the impact of cranioplasty on syndrome of the trephined or “sinking flap syndrome.” This syndrome refers to the neurological deterioration that occurs after a large craniectomy, with various symptoms including headaches, motor weakness, worsened hemisyndrome, language deficits, and cognitive disorders with or without an orthostatic component. These symptoms can improve or resolve entirely as early as 3–4 days after a cranioplasty [ 1 , 2 , 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, awareness of SSFS is poor outside of the neurosurgery community. 2 One systematic review of the literature found that the most common indication for craniectomy is traumatic brain injury (43%), followed by tumor resection (23%), intracerebral hemorrhage (11%), and aneurysmal subarachnoid hemorrhage (2%). 2 Following craniectomy, SSFS can occur within a few days or up to a year after.…”
mentioning
confidence: 99%